Optimasi Formula Blending Produk Marine Fuel Oil Low Sulfur (MFO-LS) untuk Pemenuhan Bahan Bakar Kapal Berstandar International Maritim Organization (IMO) 2020 - Fitra Dhuha; Reza Fauzan; Teuku Rihayat (Jurnal Teknologi, 2026)
This study aims to optimize the blending formulation of Marine Fuel Oil Low Sulfur (MFO-LS) to comply with the International Maritime Organization (IMO) 2020 regulation, which limits sulfur content to a maximum of 0.50% m/m. The methodology involves optimization using the Generalized Refining Transportation Marketing Planning System (GRTMPS) software, followed by laboratory validation of four blending formulations. The evaluated parameters include kinematic viscosity, pour point, flash point, density, sulfur content, and other impurities based on ASTM and ISO 8217 standards. The results indicate that not all formulations met the required specifications. Blending 1 exhibited a high pour point issue, while Blending 2 failed to meet the minimum viscosity requirement. The optimal formulation was achieved in Blending 3, which utilized 40% short residue combined with distillate components such as kerosene, LVGO, and HVGO. This formulation successfully met all critical parameters, with a viscosity of 87 mm²/s, pour point of 24°C, flash point of 66°C, and sulfur content of 0.2% m/m. The findings also demonstrate that HVGO can be effectively utilized as a blending component within a 5–10% volume range without compromising product quality. Furthermore, the reformulation improves operational efficiency and economic value by maximizing the utilization of low-value residue streams. Therefore, the proposed blending strategy provides a practical and effective solution to meet global environmental regulations while enhancing the competitiveness of marine fuel products.